Evaluating the Effectiveness of Physics Olympiad Training: A Pretest-Posttest Study Among High School Students in East Kalimantan - Charlos Falentino; Alphero Tanlianto; Evanita Mutang (Program Studi Pendidikan Fisika, 2024)
The opportunity to learn and achieve is the right of all Indonesian students. The National Science Olympiad (OSN) is a government event to improve student learning achievement, but OSN participation and preparation is still limited, especially for East Kalimantan students. This community service supports the preparation of 71 students from 10 cities in East Kalimantan in facing the Physics OSN through online training for one week via Zoom. Analysis of student understanding through Pre-test and Post-test, with binomial statistical tests, showed a significant increase in the post-test, indicating success in improving understanding of physics concepts. Several students from this program successfully advanced to the provincial OSN. To support inclusivity, facilities and teaching quality need to be improved.